AB0530 Prevalance of osteonecrosis of bone in patients of SLE in a newly established rheumatology clinic in central india. (15th June 2017) - Malviya, S; Gupta, N; Gupta, R
Abstract : Background: Osteonecrosis (OCN) is a well recognized complication of SLE. The prevalence rate of AVN in SLE ranges from 8–25% in various studies. It is always debatable if corticosteroids or disease itself causes OCN. Although long term corticosteroids use can cause OCN, but in few cases and studies it has shown disease itself can be the causative event. Objectives: To study the prevalance of Osteonecrosis of bone among patients of SLE attending the newly established Rheumatology clinic over 2 years time. Methods: All the patients of SLE with OCN attending the newly established Rheumatology clinic of the town were included in the study.OCN was diagnosed on the basis of MRI after screening with X-ray.Serological data collected. Routine investigations done were collected. Details of patients were included in a set proforma and details noted in the same. Results: Among 180 patients of SLE were included in the study. Among those, 9 patients (5%) were diagnosed with OCN. Seven patients of OCN had been on steroids but 2 patients never received any drugs, both were male. All the patients were AN A positive (Homegenous pattern in 6 and Speckled in 3), Anti-ds-DNA was positive in 7 and Anti-Smith in 2. Most common site of OCN was Femur head (n=6), Lower femoral condyles in 2 patinets of OCN and head of Talus in 1. Anti-phospholipid antibodies were found in 3 patients. Conclusions: Osteonecrosis was found in 5% of patients of SLE. Most of the patients had active disease with OCN occurred very early during the course of disease. This suggest OCN can be seen due to disease itself as 2 patients never received any drugs. Most common antibodies associated was anti ds-DNA antibody. So among patients of SLE with hip or pain in joints/bone not explaining active arthritis, OCN should be ruled out. References: Lam G.K.W, Petri M. Assessment of Systemic Lupus Erythematosus. Clin Exp Rheumatol 2005;23 (Suppl. 39): S120–132. Mont MA, Glueck CJ, Pacheco IH, Wang P, Hungerford DS, Petri M. Risk factors for osteonecrosis in systemic lupus erythematosus. J Rheumatol 1997;24:654–62. Petri M. Musculoskeletal complications of systemic lupus erythematosus in the Hopkins Lupus Cohort: an update. Arthritis Care Res 1995;8:137–45. Dubois EL, Cozen L. Avascular (aseptic) bone necrosis associated with systemic lupus erythematosus. JAMA 1960;174:966–71. Harrington KD, Murray WR, Kountz SL, Belzer FD. Avascular necrosis of bone after renal transplantation. J Bone Joint Surg Am 1971;53:203–15. Murray WR. Hip problems associated with organ transplants. Clin Orthop 1973;90:57–69. Heimann WG, Freiberger RH. Avascular necrosis of the femoral and humeral heads after high dosage corticosteroid therapy. N Engl J Med 1960;263:672–5. Abeles M, Urman JD, Rothfield NF. Aseptic necrosis of bone in systemic lupus erythematosus. Relationship to corticosteroid therapy. Arch Intern Med 1978;138:750–4. Acknowledgements: Dr Arvind Rawal: Orthopaedician. Dr Mallika Kwatra- Pathologist Dr Sandeep Shrivastava- Director Disclosure of Interest: None declared